2004
DOI: 10.1074/jbc.m402934200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the L6–7 Loop in SERCA1a Ca2+-ATPase Activation by Ca2+ (or Sr2+) and ATP

Abstract: Wild-type (WT) and the double mutant D813A,D818A (ADA) of the L6 -7 loop of SERCA1a were expressed in yeast, purified, and reconstituted into lipids. This allowed us to functionally study these ATPases by both kinetic and spectroscopic means, and to solve previous discrepancies in the published literature about both experimental facts and interpretation concerning the role of this loop in P-type ATPases. We show that in a solubilized state, the ADA mutant experiences a dramatic decrease of its calcium-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 84 publications
1
31
0
Order By: Relevance
“…4). From a methodological point of view it is of interest that we found that under appropriate conditions (40% glycerol added to Ca 2ϩ -ATPase solubilized by 1 mg/ml DDM) information could be obtained directly from the detergent-solubilized state, obviating the need to go through the complete reconstitution procedure used previously (15,36). In addition to confirming the reliability of the previous measurement of an ATP affinity in the nanomolar Ϫ and AMPPCP are also apparent in the difference map albeit at lower (3.0 ) contour level, not shown.)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). From a methodological point of view it is of interest that we found that under appropriate conditions (40% glycerol added to Ca 2ϩ -ATPase solubilized by 1 mg/ml DDM) information could be obtained directly from the detergent-solubilized state, obviating the need to go through the complete reconstitution procedure used previously (15,36). In addition to confirming the reliability of the previous measurement of an ATP affinity in the nanomolar Ϫ and AMPPCP are also apparent in the difference map albeit at lower (3.0 ) contour level, not shown.)…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the functional consequences of mutations has reached a level where it encompasses rapid kinetic quench-flow studies of the partial reaction steps (28) and most recently also biophysical measurements of conformational transitions by fluorescence changes, made feasible by large scale expression in yeast (15,29). A number of mutations appear to accelerate or block partial reactions in the functional cycle and displace E1-E2 and/or E1P-E2P equilibria.…”
mentioning
confidence: 99%
“…Phosphorylation Assay-Phosphorylation from [␥-32 P]ATP was performed as described (29,30) on purified H 2 -Drs2p preincubated with 1 mg/ml dioleoylphosphatidyl choline/dioleoylphosphatidic acid (9/1) in MOPS buffer (50 mM MOPSTris, pH 7.0, 100 mM KCl, 5 mM MgCl 2 , 0.05% digitonin) for 1 h at 4°C under gentle agitation. One g/ml H 2 -Drs2p (ϳ0.1 g/reaction) in MOPS buffer supplemented with 6 units/ml pyruvate kinase was incubated at 4°C for 50 supplemental Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Noting that crystal structures represent "frozen" conformations characterized by exceptional stability under certain nonphysiological conditions, it is important to ask the question whether the hydrogen bond interactions apparent from the crystal structures also occur in the native enzyme during the transport cycle, and whether they are functionally important. (13)(14)(15)(16)(17) and of insensitivity to regulation by phospholamban in point mutant D813A (18). In preliminary work (19), we have demonstrated that point mutant D813L exhibits a much larger phosphorylation overshoot than the wild type, upon reaction of the Ca 2ϩ -bound enzyme with ATP.…”
mentioning
confidence: 97%